2013
DOI: 10.1186/1754-6834-6-140
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of plant growth and seed yield in Jatropha curcas by a novel nitrogen-fixing root associated Enterobacter species

Abstract: BackgroundJatropha curcas L. is an oil seed producing non-leguminous tropical shrub that has good potential to be a fuel plant that can be cultivated on marginal land. Due to the low nutrient content of the targeted plantation area, the requirement for fertilizer is expected to be higher than other plants. This factor severely affects the commercial viability of J. curcas.ResultsWe explored the feasibility to use endophytic nitrogen-fixing bacteria that are native to J. curcas to improve plant growth, biomass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 73 publications
3
28
0
1
Order By: Relevance
“…R4‐368 is an acclaimed potential plant growth promoting bacterium that colonizes J . curcas root and stem tissues . In the present study, as many as eight of the 11 isolates (GSL‐01, ‐02, ‐03, ‐04, ‐05, ‐06, ‐07, and 11) showed maximum similarity with the Enterobacter sp.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…R4‐368 is an acclaimed potential plant growth promoting bacterium that colonizes J . curcas root and stem tissues . In the present study, as many as eight of the 11 isolates (GSL‐01, ‐02, ‐03, ‐04, ‐05, ‐06, ‐07, and 11) showed maximum similarity with the Enterobacter sp.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, nitrogen fixing Enterobacter sp. from the Jatropha curcas oil seed producing non‐leguminous tropical shrub plant was also reported . However, Enterobacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in contrast with the present study, where Bacillus and Enterobacter were found to be the dominant genera of rhizospheric bacteria and Enterobacter was found to be the dominant genus of endophytic bacteria. Madhaiyan et al (2013) studied endophytic bacteria isolated from Jatropha curcas roots from Indonesia, China and India and observed a predominance of strains from genus Enterobacter, such as the species E. oryzae, E. asburiae, E. cancerogenus, E. cloacae, E. aerogenes and E. ludwigii, which were also found in the present study, with several only found in the endophytic environment and others found in both environments.…”
Section: Discussionsupporting
confidence: 64%
“…Este fenómeno posiblemente se deba a la cantidad y la calidad de los derivados de carbono y las sustancias promotoras provenientes de la raíz, que favorecen el aumento de la biomasa microbiana fijadora de nitrógeno (Ravikumar et al 2004 (Madhaiyan et al 2013). …”
Section: -351unclassified